PENGARUH RELATIONSHIP MARKETING TERHADAP LIFETIME VALUE PADA PT. SOPHIE MARTIN BUSINESS CENTRE CITRA SEMARANG - Eka Runi Anggita; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2016)
The success in the competitive world of business will be fulfilled by creating and maintainingconsumers, because the strategies used are to build customer loyalty. Customer loyalty is a real phenomenonthat is constantly pursued by any company to maintain the existence of its business. This study aimed todetermine the impact of communication, trust, commitment, and problem resolution toward the lifetime valueeither partially or simultaneously. The type of this research is associative research in order to discover therelationship between variables, in addi tion to test the hypothesis, then taken sample of 100 members of PT.Sophie Martin Business Centre Semarang as respondents using slovin formulas and simple random samplingtechniques. Data was analysed by validity data analysis techniques, reliability test , regression, t and F test. Thecalculation results of multiple linear regression can be indicated by Y = 2.908 + 0, 253X1 + 0, 270X2 + 0,036X3 + 0, 025X4. Partially the influence of trust to the lifetime value is 46.4%, the commitment to the lifetimevalue is 56.3%, the communication to the lifetime value of 65.5% and the problem resolution to the lifetimevalue of 21.6%. Simultaneously the impact of trust, commitment, communication, and problem resolution tolifetime value amounted to 35.4%. To increase the lifetime value, companies must define service standards,accept criticism and suggestions from members, conduct gatherings, optimize the use of technology, and solvethe problem with the win-win solution principle.